Teknologi Komposter dan Digester untuk Optimasi Pengolahan Sampah Organik Bagi Warga Desa Tempursari Kecamatan Donomulyo Kabupaten Malang - Nurmalasari, Riana; Sutadji, Eddy; Aji Sunaryo, Nonny; Viona P.P.S, Gladis (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2023)
Environmental well-being is significantly impacted by public consciousness regarding waste management.   Households must be conscious of their ability to effectively utilize and manage waste before disposing of it in a landfill.   Tempursari Village, located in Donomulyo District, is a promising area in Malang Regency for implementing waste processing technology. This is due to the abundance of organic waste that remains unmanaged and underutilized.  The technologies in question are composters and digesters.   The implementation of composter and digester technology in Tempursari village results in a 55% reduction of organic waste generated by each household.   Previously unprocessed trash is now directly deposited into the composter bin for processing.   The application of composter technology extends beyond the management of organic waste.   Nevertheless, it is currently undergoing further development as a substrate for planting.   Using digester technology, it was discovered that each digester tube with a volume of 150-200 litres could produce biogas with a capacity of 500 litres. This biogas could be utilized for cooking purposes within a time frame of 60 to 120 minutes.   These findings significantly contribute to the community's endeavours to minimize the utilization of LPG gas.